The roles of the zinc finger transcription factors XlnR, ClrA and ClrB in the breakdown of lignocellulose by Aspergillus niger - Raulo, Roxane; Archer, David B.; Kokolski, Matthew (SpringerOpen, 2016)
Genes encoding the key transcription factors (TF) XlnR, ClrA and ClrB were deleted from Aspergillus niger and the resulting strains were assessed for growth on glucose and wheat straw, transcription of genes encoding glycosyl hydrolases and saccharification activity. Growth of all mutant strains, based in straw on measurement of pH and assay of glucosamine, was impaired in relation to the wild type (WT) strain although deletion of clrA had less effect than deletion of xlnR or clrB. Release of sugars from wheat straw was also lowered when culture filtrates from TF deletion strains were compared with WT culture filtrates. Transcript levels of cbhA, eglC and xynA were measured in all strains in glucose and wheat straw media in batch culture with and without pH control. Transcript levels from cbhA and eglC were lowered in all mutant strains compared to WT although the impact of deleting clrA was not pronounced with expression of eglC and had no effect on xynA. The impact on transcription was not related to changes in pH. In addition to impaired growth on wheat straw, the ΔxlnR strain was sensitive to oxidative stress and displayed cell wall defects in the glucose condition suggesting additional roles for XlnR. The characterisation of TFs, such as ClrB, provides new areas of improvement for industrial processes for production of second generation biofuels.